2020
DOI: 10.1038/s41467-020-17278-2
|View full text |Cite
|
Sign up to set email alerts
|

Pathways for horizontal gene transfer in bacteria revealed by a global map of their plasmids

Abstract: Plasmids can mediate horizontal gene transfer of antibiotic resistance, virulence genes, and other adaptive factors across bacterial populations. Here, we analyze genomic composition and pairwise sequence identity for over 10,000 reference plasmids to obtain a global map of the prokaryotic plasmidome. Plasmids in this map organize into discrete clusters, which we call plasmid taxonomic units (PTUs), with high average nucleotide identity between its members. We identify 83 PTUs in the order Enterobacterales, 28… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
336
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 271 publications
(357 citation statements)
references
References 70 publications
20
336
0
1
Order By: Relevance
“…While this diversity can be representative of certain clinical samples [79][80][81], other environments with relevance to public health, such as the human gut, soil and livestock, can have 100-1000s of species [82][83][84][85]. In addition, MGEs such as GIs and plasmids are known to recombine, producing closely related variants [86][87][88] that could further complicate assembly from a metagenomic sample. Polymorphic MGEs were not explicitly introduced in our simulated metagenome.…”
Section: Discussionmentioning
confidence: 99%
“…While this diversity can be representative of certain clinical samples [79][80][81], other environments with relevance to public health, such as the human gut, soil and livestock, can have 100-1000s of species [82][83][84][85]. In addition, MGEs such as GIs and plasmids are known to recombine, producing closely related variants [86][87][88] that could further complicate assembly from a metagenomic sample. Polymorphic MGEs were not explicitly introduced in our simulated metagenome.…”
Section: Discussionmentioning
confidence: 99%
“…This enhances the potential for plasmid spread and maintenance dramatically, even when it was reported to be very low for a specific plasmid-host-combination. This finding is of particular importance considering that recent bioinformatic analysis revealed that more than 60% of the plasmids of the global prokaryotic plasmidome were reported to be able to colonize species from different phyla [58] . Plasmids coding for antibiotic resistance could therefore initially acquire cost-compensating mutations in co-evolution with a particular common host and later spread as optimized vectors to other less common but potentially more harmful species.…”
Section: Plasmid Fitnessmentioning
confidence: 93%
“…Plasmid clustering algorithm (sHSBM). The PTU definition algorithm was based on a DNA homology network constructed from the pairwise comparison of all RefSeq84 plasmids (NCBI, dataset from September 2017), using Average Nucleotide Identity (ANI), as detailed in (2). An edge was drawn between two plasmid nodes if homology was detected over 50% of the shorter genome length.…”
Section: Methodsmentioning
confidence: 99%
“…Only clusters with at least four members were considered representative enough to be included in the next step. A home-made algorithm was added in (2) to join the previously divided clusters into a single PTU if two biological specifications were met:…”
Section: Methodsmentioning
confidence: 99%